Pharmacy Interns' Perception of Climate Change and Its Impact on Health - Cecilia Speck; Natalie DiPietro Mager; John Mager (University of Minnesota Libraries Publishing, 2024)
Background: The effects of climate change are major threats to health and well-being. While the profession of pharmacy can make a difference through patient care activities or sustainability and advocacy efforts, literature detailing U.S. pharmacist and student pharmacist views on this topic is scant. Objectives: To assess Ohio pharmacy interns' knowledge and beliefs regarding climate change and human health as well as its relevance to pharmacy practice and education, and to compare and contrast their perceptions with those of Ohio pharmacists previously surveyed. Methods: An anonymous 31-item electronic survey was emailed to a random sample of 500 pharmacy interns registered in Ohio with questions regarding climate change and health, climate change policy, potential roles for pharmacists and pharmacy interns, pharmacy education, and selected demographics. Data were analyzed using descriptive and nonparametric statistics, and responses collected from this study were compared with those from the Ohio pharmacist study conducted the previous year. Results: Ninety-two interns completed the survey. The majority of respondents thought climate change is happening (87%), will harm human health in their community (68%), and is relevant to pharmacists or pharmacy practice (62%). Compared to registered pharmacists, pharmacy interns more often acknowledged these statements and more often identified roles in climate action. Sixty-two percent somewhat or strongly agreed that there should be more education about climate change and health in the pharmacy curriculum. Conclusion: Ohio pharmacy interns participating in this survey recognized the impact of climate change on health, believed they roles in mitigating its effects, and wanted to learn more about it. As these are the first data assessing U.S. pharmacy interns' perceptions of this topic, additional studies should be performed in other parts of the country. Increased education among student pharmacists may help propel the pharmacy profession to become a leader in climate action and sustainability.